2013
DOI: 10.1007/978-3-319-03841-4_39
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Grid-Like Layout Using Soft and Hard Constraints

Abstract: Abstract. We explore various techniques to incorporate grid-like layout conventions into a force-directed, constraint-based graph layout framework. In doing so we are able to provide high-quality layout-with predominantly axis-aligned edges-that is more flexible than previous grid-like layout methods and which can capture layout conventions in notations such as SBGN (Systems Biology Graphical Notation). Furthermore, the layout is easily able to respect user-defined constraints and adapt to interaction in onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…The most closely related approach is that of Kieffer et al [20] which explores the use of greedy heuristics to "gridify" a force-directed layout by snapping nodes to a grid or adding vertical or horizontal alignment constraints between nodes, and Rüegg et al [31] which extends this to handle port constraints and directed edges laid out using orthogonal connectors. While stages 2b and 4a of HOLA utilise similar greedy heuristics, these are a small part of the overall approach.…”
Section: Human-like Orthogonal Layout Algorithm (Hola)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most closely related approach is that of Kieffer et al [20] which explores the use of greedy heuristics to "gridify" a force-directed layout by snapping nodes to a grid or adding vertical or horizontal alignment constraints between nodes, and Rüegg et al [31] which extends this to handle port constraints and directed edges laid out using orthogonal connectors. While stages 2b and 4a of HOLA utilise similar greedy heuristics, these are a small part of the overall approach.…”
Section: Human-like Orthogonal Layout Algorithm (Hola)mentioning
confidence: 99%
“…As a configurable option, the ACA algorithm [20] may be applied to the chains instead of this process. We have found that this gives better results on large graphs as in our second user study (see Sec.…”
Section: Layout Of the Corementioning
confidence: 99%
“…Kieffer et al [KDMW13] present a force-directed, constraintbased layout for creating graphs with node and edge alignment, and demonstrate its effectiveness for interactive refinement within the interactive graph layout system Dunnart [DMW08a]. Dwyer and Wybrow developed libcola [DW18], which utilizes constraints within a force-directed graph layout [DMW08b] using stress majorization.…”
Section: Constraint-based Layout Techniquesmentioning
confidence: 99%
“…We implemented the "grid-snap" technique described by Kieffer et al [30] in the cola.js [6] browser-based constraint-layout library. We extended this method to handle group-hierarchy containment inside rectangular regions using separation constraints as described in [18].…”
Section: Heuristic For Larger Networkmentioning
confidence: 99%
“…This approach does not allow group information to be taken into account, and the graph structure is hard to conceive from the layouts. Recent work from Kieffer et al [30] explored augmenting the objective function of a constrainedforce-directed technique to prefer nodes placed at grid-points, thereby creating a compromise between a grid-aesthetic and R2. This method (extended to grouped graphs) provides the starting point for our LNS.…”
Section: Related Workmentioning
confidence: 99%